Review: Balancing Selection for Deleterious Alleles in Livestock - Derks, Martijn F. L.; Steensma, Marije (Frontiers in Genetics, 2021)
Harmful alleles can be under balancing selection due to an interplay of artificial selection for the variant in heterozygotes and purifying selection against the variant in homozygotes. These pleiotropic variants can remain at moderate to high frequency expressing an advantage for favorable traits in heterozygotes, while harmful in homozygotes. The impact on the population and selection strength depends on the consequence of the variant both in heterozygotes and homozygotes. The deleterious phenotype expressed in homozygotes can range from early lethality to a slightly lower fitness in the population. In this review, we explore a range of causative variants under balancing selection including loss-of-function variation (i.e., frameshift, stop-gained variants) and regulatory variation (affecting gene expression). We report that harmful alleles often affect orthologous genes in different species, often influencing analogous traits. The recent discoveries are mainly driven by the increasing genomic and phenotypic resources in livestock populations. However, the low frequency and sometimes subtle effects in homozygotes prevent accurate mapping of such pleiotropic variants, which requires novel strategies to discover. After discovery, the selection strategy for deleterious variants under balancing selection is under debate, as variants can contribute to the heterosis effect in crossbred animals in various livestock species, compensating for the loss in purebred animals. Nevertheless, gene-assisted selection is a useful tool to decrease the frequency of the harmful allele in the population, if desired. Together, this review marks various deleterious variants under balancing selection and describing the functional consequences at the molecular, phenotypic, and population level, providing a resource for further study.